Implementasi Mawaris dalam Kehidupan Modern: Upaya Meraih Keberkahan melalui Pembagian Harta Waris Islam - Qorri Asyifah; Quratul A’yun; Qurratul Aini; Ridwal Trisoni; Muhamad Yahya (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study analyzes the implementation of Islamic inheritance law (mawaris) in contemporary Muslim society as a means to realize justice and blessing (barakah) in the distribution of inherited wealth. The research is motivated by the growing number of inheritance disputes caused by limited understanding of faraid principles, the persistence of customary inheritance practices, and the coexistence of national legal systems that often diverge from Islamic inheritance regulations. These conditions frequently lead to unequal distribution and family conflicts. The study aims to examine the relevance of mawaris in modern contexts and to explore how its application, when aligned with the objectives of Islamic law (maqasid al-shariah), can address current social challenges. Employing a qualitative method with a normative library research approach, the study draws on primary sources such as the Qur’an, Hadith, and classical fiqh texts, as well as secondary sources including contemporary books and scholarly journal articles. Data were analyzed through content analysis to identify key concepts and arguments regarding the contemporary application of mawaris. The findings show that proper implementation of Islamic inheritance law fosters justice, minimizes family disputes, strengthens kinship ties, and safeguards the blessing of wealth. Nevertheless, insufficient public literacy on Islamic inheritance law and the dominance of non-sharia considerations remain significant barriers. Therefore, the study underscores the need for enhanced public education, greater involvement of religious scholars in inheritance mediation, and contextual integration of Islamic legal principles to ensure fair and beneficial inheritance distribution in modern Muslim families.